Answer:
![14x cos((1)/(15)x^(2))=14 \sum _(k=0) ^(\infty) ((-1)^(k)x^(4k+1))/((2k)!15^(2k))](https://img.qammunity.org/2022/formulas/mathematics/college/6sar1dst5oienf2ab9tn0u9sdag5xl6mbl.png)
Explanation:
In order to find this Maclaurin series, we can start by using a known Maclaurin series and modify it according to our function. A pretty regular Maclaurin series is the cos series, where:
![cos(x)=\sum _(k=0) ^(\infty) ((-1)^(k)x^(2k))/((2k)!)](https://img.qammunity.org/2022/formulas/mathematics/college/kyuzndd79tvwqp23jvaesxwawllmshu40c.png)
So all we need to do is include the additional modifications to the series, for example, the angle of our current function is:
so for
![cos((1)/(15)x^(2))](https://img.qammunity.org/2022/formulas/mathematics/college/k5jfhs82isy5t2dttbhtrlw336kaiihh44.png)
the modified series will look like this:
![cos((1)/(15)x^(2))=\sum _(k=0) ^(\infty) ((-1)^(k)((1)/(15)x^(2))^(2k))/((2k)!)](https://img.qammunity.org/2022/formulas/mathematics/college/bfve95au3lf10i4b7d6vzecuykrjwr47ap.png)
So we can use some algebra to simplify the series:
![cos((1)/(15)x^(2))=\sum _(k=0) ^(\infty) ((-1)^(k)((1)/(15^(2k))x^(4k)))/((2k)!)](https://img.qammunity.org/2022/formulas/mathematics/college/er8xt6sl0efcjhqc05bb5y2qs6nagujonf.png)
which can be rewritten like this:
![cos((1)/(15)x^(2))=\sum _(k=0) ^(\infty) ((-1)^(k)x^(4k))/((2k)!15^(2k))](https://img.qammunity.org/2022/formulas/mathematics/college/serb9yffsjeofxjqn717cg8kgq3hsk3b9b.png)
So finally, we can multiply a 14x to the series so we get:
![14xcos((1)/(15)x^(2))=14x\sum _(k=0) ^(\infty) ((-1)^(k)x^(4k))/((2k)!15^(2k))](https://img.qammunity.org/2022/formulas/mathematics/college/tpb96sdl54srgaridcsg6mr81cjcj8zw7o.png)
We can input the x into the series by using power rules so we get:
![14xcos((1)/(15)x^(2))=14\sum _(k=0) ^(\infty) ((-1)^(k)x^(4k+1))/((2k)!15^(2k))](https://img.qammunity.org/2022/formulas/mathematics/college/3ov8w2mgwz6va61xhpcpe2ofq7yyz5c87k.png)
And that will be our answer.